VD_FINDINFO Décision / 2013 / 940 vom 12. August 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, FRAIS DE LA PROCÉDURE, PRÉVENU, ACQUITTEMENT | 319 CPP (CH), 395 let. b CPP (CH), 426 al. 2 CPP (CH)